Synthesis of 4,6-Unsubstituted 2-Aminodihydropyrimidine-5-carboxylates through Sequential Staudinger/Aza-Wittig/Cyclization Reactions - Nishimura, Yoshio; Cho, Hidetsura (Synlett, 2015)
A novel method for constructing the dihydropyrimidine skeleton is developed. The method involves three sequential reactions: (1) the Staudinger reaction of (E)-ethyl 3-azido-2-{[(tert-butoxycarbonyl)amino]methyl}acrylate with triphenylphosphine; (2) aza-Wittig reaction of the resulting iminophosphorane with isocyanate; (3) intramolecular cyclization of the carbodiimide intermediate to give 4,6-unsubstituted 2-aminodihydropyrimidine-5-carboxylates in high overall yield. The method can be applied to various aromatic isocyanates, with substrates having electron-withdrawing groups showing high reactivities. In the case of aliphatic benzyl isocyanate, the reaction provides bicyclic dihydropyrimidine as the major product. The N-protecting group (Boc) can easily be removed to obtain N-unsubstituted dihydropyrimidines. All dihydropyrimidines in this study were previously unavailable and are difficult to synthesize by conventional methods.
Keywords: dihydropyrimidine; heterocycles; Staudinger reaction; aza-Wittig reaction; cyclization